Physico-chemical and Bacteriological Characteristics of Señora River, Siquijor Island, Central Philippines - Paculba, Hermilita L.; Catid, Rosalina E.; Tan, Ronald Alexis L.; Barrera, Glory J.; Aque, Septima C.; Barrera, Diogenes M. (Silliman Journal, 2022)
The water quality of Señora River in Lazi, Siquijor, Philippines was assessed in terms of its physico-chemical and bacteriological (Escherichia coli) characteristics. The study aimed to establish baseline data on its water quality for future studies. It also determined the spatial and seasonal variation of the parameters used. Sampling was done in the upstream, midstream, and downstream sections of the river from February to July 2011. Major findings are as follows: [1] all values of the parameters monitored are within the permissible limits (based on the standards set by the DENR, except for E. coli; [2] there is no significant difference in the spatial variation (among the three stations) of dissolved oxygen (DO), salinity, water sub-surface temperature, water surface temperature, nitrates-N, phosphates-P, and E. coli contents [however, levels of total dissolved solids (TDS), pH, and conductivity of the river are significantly higher in the downstream station]; [3] there is no significant difference in the seasonal (wet and dry months) variation of all the parameters; and [4] Based on E. coli content of the water, Señora River failed to meet standards set by the Philippine National Standard for Drinking Water (PNSDW). The middle and downstream part of the river can be classified as Class B and C intended for primary contact recreation such as bathing and swimming only.